Effect of extraction solvent on total flavonoid content of andaliman fruit (Zanthoxylum acanthopodium DC): PENGARUH EKSTRAKSI DENGAN PELARUT PADA TOTAL FAVONOID BUAH ADALIMAN (Zanthoxylum acanthopodium DC) - Septina Silalahi; Tory Rachel Megaputri; Daisy . (Pro Food, 2019)
Hypertension is a disease where blood pressure increases chronically beyond normal limits. Hypertension needs to be watched out because it includes asymptomatic diseases and can cause complications. One alternative treatment for hypertension that has been proven effective in the pharmaceutical industry is the use of ACE-I (Angiotensin-I Converting Enzyme Inhibitors). At present, ACE-I synthesis has been produced commercially as an antihypertensive drug, for example captopril, enalapril, alcacepril, and lisinopril. However, there are many studies that show the existence of ACE-I synthesis side effects for its users, both physiological and non-physiological effects such as coughing, angioedema, and disorders in pregnancy. ACE-I obtained naturally is safer than ACE-I synthesis. Research on ACE-I activity from natural ingredients is still very limited. Andaliman (Zanthoxylum acanthopodium DC) or better known as Batak Pepper has the potential as a natural source of ACE-I. Natural ACE-I in Andaliman can be obtained from the flavonoid content of Andaliman fruit extract. The purpose of this study was to determine total flavonoid content in andaliman fruit by comparing the types of solvents used for extraction. The solvents used were N-hexane, ethyl acetate, ethanol, and water. The extraction results were then compared using a completely randomized design (CRD) to determine the success of this study. Keywords: Antihypertensive, flavonoids, flavonoid, Zanthoxylum acanthopodium DC ABSTRAK Hipertensi adalah penyakit di mana tekanan darah meningkat secara kronis di luar batas normal. Hipertensi perlu diwaspadai karena termasuk penyakit tanpa gejala dan dapat menyebabkan komplikasi. Salah satu pengobatan alternatif untuk hipertensi yang telah terbukti efektif dalam industri farmasi adalah penggunaan ACE-I (Angiotensin-I Converting Enzyme Inhibitors). Saat ini, sintesis ACE-I telah diproduksi secara komersial sebagai obat antihipertensi, misalnya captopril, enalapril, alcacepril, dan lisinopril. Namun, ada banyak penelitian yang menunjukkan adanya efek samping sintesis ACE-I bagi penggunanya, baik efek fisiologis dan non-fisiologis seperti batuk, angioedema, dan gangguan pada kehamilan. ACE-I yang diperoleh secara alami lebih aman daripada sintesis ACE-I. Penelitian tentang aktivitas ACE-I dari bahan-bahan alami masih sangat terbatas. Andaliman (Zanthoxylum acanthopodium DC) atau lebih dikenal dengan sebutan Batak Lada berpotensi sebagai sumber alami ACE-I. ACE-I alami di Andaliman dapat diperoleh dari kandungan flavonoid dari ekstrak buah Andaliman. Tujuan dari penelitian ini adalah untuk menentukan total flavonoid dalam buah andaliman dengan membandingkan jenis pelarut yang digunakan untuk ekstraksi. Pelarut yang digunakan adalah N-heksana, etil asetat, etanol, dan air. Hasil ekstraksi kemudian dibandingkan dengan menggunakan desain acak lengkap (CRD) untuk menentukan keberhasilan penelitian ini. Kata kunci: Antihipertensi, flavonoid, flavonoid, Zanthoxylum acanthopodium DC